Development of a real‐time PCR assay for detection and differentiation of Mycoplasma ovipneumoniae and a novel respiratory‐associated Mycoplasma species in domestic sheep and goats. Issue 5 (23rd February 2022) - Noll, Lance W.; Highland, Margaret A.; Hamill, Vaughn A.; Tsui, Wai Ning Tiffany; Porter, Elizabeth P.; Lu, Nanyan; Sebhatu, Tesfaalem; Brown, Susan; Herndon, David R.; Grossman, Paige C.; Bai, Jianfa
Abstract: A novel respiratory‐associated Mycoplasma species ( M . sp. nov.) of unknown clinical significance was recently identified that causes false positive results with multiple published PCR methods reported to specifically detect Mycoplasma ovipneumonaie, a well‐known respiratory pathogen in small ruminants. This necessitates our objective to develop a real‐time PCR (qPCR) assay for improved specificity and sensitivity, and more rapid detection and differentiation of M. ovipneumoniae and the M . sp. nov. in domestic sheep (DS) and domestic goat (DG) samples, as compared to a conventional PCR and sequencing (cPCR‐seq) assay. Primers and probes were designed based on available M. ovipneumoniae 16S rRNA gene sequences in the GenBank database, and partial 16S rRNA gene sequences provided by the United States Department of Agriculture, Agricultural Research Service (USDA‐ARS) for M. ovipneumoniae and M . sp. nov. USDA‐ARS provided DS ( n = 153) and DG ( n = 194) nasal swab nucleic acid that previously tested positive for either M. ovipneumoniae ( n = 117) or M . sp. nov. ( n = 138), or negative for both targets ( n = 92) by cPCR‐seq. A host 18S rRNA gene was included as an internal control to monitor for the failure of nucleic acid extraction and possible PCR inhibition. For samples positive by cPCR‐seq, qPCR agreement was 88.0% (103/117; κ = 0.81) and 89.9% (124/138; κ = 0.84) for M. ovipneumoniae and M . sp. nov., respectively; 12 of 255 (4.7%) cPCR‐seq positive samples were qPCR positive for both targets. Of samples negative by cPCR for both mycoplasmas, qPCR detected M. ovipneumoniae and M . sp. nov. in 6.5% (6/92) and 4.3% (4/92), respectively. Samples with discordant results between the cPCR and sequencing assay and the new qPCR were analyzed by target sequencing; successfully sequenced samples had identity matches that confirmed the qPCR result. The increased target specificity of this qPCR is predicted to increase testing accuracy as compared to other published assays.